Resumption of Marriage Nullity Case: Canons 1522 and 1525 - Schöch, Nikolaus (CLSA advisory opinions, 2001-2005, 2001)
Is it possible to resume a matrimonial cause at another tribunal after it has been shelved because of lack of activity by the parties or by renunciation?